Valores da economia solidária e suas implicações no estabecimento dos vínculos organizacionais e sociais - Santos, Rita de Cássia Trindade dos (2018)
This paper has as general objective to analyze the relations between the values attributed to the solidarity economy and the establishment of the organizational and social linkages in the perspective of the workers of solidary economic enterprises. Thus, a research was subdivided into two phases, the first of quantitative approach, conclusive descriptive and exploratory nature by means of the survey method, based on the application of the Scale of Values of the Solidarity Economy de Guerra (2014), Organizational Commitment Measure of Bastos and Aguiar (2015) and Organizational Entrenching Measure (MEO) of Rodrigues and Bastos (2015) with frequency analysis, descriptive statistics, exploratory factorial analysis, Pearson correlation and Cluster analysis. The second phase of the research was a qualitative approach, an integrated single case study method whose data were collected by a semi-structured interview script based on the categories of social linkages proposed by Gaiger (2016) with content analysis of the reports. The results indicated respondents with high levels of identification with most values of the solidarity economy, except for citizenship, and organizational commitment followed by medium and low level in the dimensions of organizational entrenchment. Adherence to the values of quality of life and identification, citizenship and solidarity and self-management of solidarity economy corroborates positively to the bond of organizational commitment. On the other hand, the value of citizenship had a negative association with the limitation of alternatives. The social linkages found tend to be group-like, formed by fusion ties of identity, economic relations of cooperation, economic principle of reciprocity and forms of class and family solidarity. The findings in the qualitative phase allowed to clarify some notes of the quantitative phase. Thus it was concluded that when the commitment stands out together with the self-management the sense of collective responsibility for the management is strengthened by overcoming motivations that are limited to achievement and individual satisfaction with work. The passivity of the workers in relation to the action in the local community by the social and political participation, found in the quantitative phase, can be linked to the understanding of what is to be the solidarity. Therefore, identification with the values of solidarity economy is a continuous process of construction that pervades individual subjectivities and is effective in the experience of collectivity. The limitations of this research are found in the recent application of the scale of values of the solidarity economy as well as in its association to the measurement of the ties of commitment and organizational entrenchment in the context of the solidarity economy. For future research it is suggested the continuity of the discussion about the bonds of the worker with the solidary economic enterprises, be they organizational and / or social, in order to meet the assumptions that guide such organizations.